Pt nanoparticles supported on Nb-modified TiO2 as an efficient heterogeneous catalyst for the conversion of cellulose to light bioalcohols. Issue 88 (19th October 2022) - Su, Zerui; Zhang, Jian; Lu, Shiyao; Xiao, Feng-Shou
Abstract : SMSI-introduced Pt/NbTi catalysts with abundant acid sites are very active for the hydrogenolysis of cellulose into light bioalcohols. Abstract : Nb-modified anatase-supported Pt nanoparticles were synthesized for the efficient conversion of cellulose to light bioalcohols. Characterization confirmed the presence of SMSIs in the catalysts, offering adjacent hydrogenation sites, Brønsted and Lewis acid sites. Treating the catalysts in humid air enhanced the acidic concentration, accelerating the key step during the reaction.